2022
DOI: 10.3390/curroncol29110638
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Indocyanine Green Compared to 99mTc-Nanocolloids for Sentinel Lymph Node Detection in Early Vulvar Cancer

Abstract: Study objective: The aim of this study was to evaluate the performance of indocyanine green (ICG) compared to that of the gold standard 99mtechnetium (99mTc-nanocolloids) in detecting sentinel lymph nodes (SLN) in early vulvar cancer. Material and Methods: A single-center retrospective cohort study comparing SLN detection by 99mTc-nanocolloids and ICG was performed in patients presenting early vulvar cancer (T1/2), with clinically negative nodes. All SLN showing a radioactive and/or fluorescent signal were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…4 One single-center study found a slightly lower sentinel detection rate compared with technetium-99 but indicated that growing experience with the method increased detection rate. 6 It has been recommended not to useindocyanine green as the sole tracer for sentinel detection but in conjunction with technetium-99, 7 and indocyanine green methodology needs to be consolidated. 8 This video consists of intra-operative video footage recorded with an indocyanine green exoscope for open surgery (Vitom-ICG, Karl Storz, Germany) with its different video modes applied: Combining radioactive tracer and indocyanine green methods simplifies sentinel lymphadenectomy in vulvar cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4 One single-center study found a slightly lower sentinel detection rate compared with technetium-99 but indicated that growing experience with the method increased detection rate. 6 It has been recommended not to useindocyanine green as the sole tracer for sentinel detection but in conjunction with technetium-99, 7 and indocyanine green methodology needs to be consolidated. 8 This video consists of intra-operative video footage recorded with an indocyanine green exoscope for open surgery (Vitom-ICG, Karl Storz, Germany) with its different video modes applied: Combining radioactive tracer and indocyanine green methods simplifies sentinel lymphadenectomy in vulvar cancer.…”
Section: Discussionmentioning
confidence: 99%
“…All clinical studies (n510) until 2023 with full-text availability were included. 23,[25][26][27][28][29][30][31][32][33] The Lateralized tumors are located .1 cm from the midline; near midline tumors are located #1 cm from the midline but not crossing the midline; true midline tumors cross the midline.…”
Section: Sn Mappingmentioning
confidence: 99%
“…Benmoulay-Rigollot et al [23] retrospectively evaluated the performance of ICG compared with that of the gold standard Tc99m in detecting SLN in early vulvar cancer. Thirty patients were included and 99 SLN were identified in 43 groins.…”
Section: Vulvar Cancermentioning
confidence: 99%
“…With regard to sensitivity, the performance of ICG appears to be insufficient compared with Tc99m in detecting SLN in patients with early-stage vulvar cancer. They concluded that despite its many advantages, ICG cannot be used as the sole tracer for the detection of SLN and should be employed in conjunction with Tc99m [23].…”
Section: Vulvar Cancermentioning
confidence: 99%